Rolling Stone Sdn Bhd / Nur Syaheera Mohd Fadhil, Nur Syafiqah Roslan and Anis Syahirah Abd Rahman - Roslan, Nur Syafiqah; Mohd Fadhil, Nur Syaheera; Abd Rahman, Anis Syahirah (2012)
This business is based on partnership where it consists of three (3) members. Job allocation was divided equally starting from the General Manager, Administration Manager, Marketing Manager, Operational Manager and lastly Financial Manager. The business capital is amounted to RM where the total contribution of each member is RM and the rest is from the Bank loan. THE ROLLING STONE is basically more into food sections. This is where we cook the food immediately when the order is proceed. Our market mainly focus is the consumers that come to visit the shopping malls. Not that they will give us benefits but they are also allowed to watch while cooking to gain experience. People are allowed to open another branch by going through the contract agreement process from the main source. Our business will be expected to commence on 2012 and our vision is to make our company a well-known, established and satisfied by our customer in order to expand our capacity of making rolling paratha with variety sauce and fillings and to attract other companies to deal with us with a better price. We are expecting to open more branches like small booths in few places for start and if it is possible we would also like to expand the menu choices in the future. It all depends from the start where it all begins to show that people or consumers like it or not.